Business process improvement using Object‐Process Methodology. Issue 1 (10th June 2019) - Casebolt, Jason M.; Jbara, Ahmad; Dori, Dov
Abstract: For decades, business process improvement (BPI) has been a persistent and expensive concern that spans across many industry sectors. We present OPM‐BPI—a model‐based method to improve business processes using ISO 19450—Object‐Process Methodology (OPM). The approach compares favorably to state‐of‐the‐art business process languages and approaches, such as Business Process Modeling Notation (BPMN). An aviation manufacturing company case study of safely removing a part from an aircraft and reinstalling it demonstrates the method. We show how using OPM‐BPI enables removing a large portion of the supporting objects, and how related processes can be eliminated or merged, achieving considerable model simplification that represents a significantly improved, more effective and less wasteful business process.